Analisis Perbandingan Nilai Penawaran Tender Proyek Konstruksi Dengan Pemodelan Gates dan Friedman (Studi Kasus: LPSE Kabupaten Bolaang Mongondow Utara) - Saviha Pahata; Mohamad Yusuf Tuloli; Arfan Utiarahman (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
The tender process in construction project procurement is pivotal for determining the success of infrastructure development A vital part of this process is the method of determining the bid price used by contractors to secure a probability of winning while also achieving optimum profit. This study aimed to analyze and compare the mark-up value, win probability, and expected profit using two bidding strategy models the Friedman Model and the Gates Model in the construction project bidding process at the North Bolaang Mongondow Regency LPSE for the 2022-2023 period. The method used was a statistical approach involving the processing of secondary data from completed project bid data. The analysis was conducted on mark-up data. and the probability of winning and expected profit were calculated for each model The analysis results revealed that each model had distinct characteristics in determining the best bidding strategy The Friedman Model tends to produce more cautious mark-up values with a stable win probability, while the Gates Model offers a bolder approach in its expected profit calculation. Thus, this study has been able to notify construction practitioners in formulating policies on the importance of selecting a bidding strategy method that aligns with market conditions and the number of competitors, thereby enhancing effectiveness in the construction project tender process.